Development of Underwater Technology in Supporting the Transformation of the Indonesian Navy’s Capabilities Based on System-Oriented Undersea Warfare - Ningsih Rezeki; Rudy Sumantri; Rina Farah (Yayasan Adra Karima Hubbi, 2026)
Background. The Indonesian Navy faces significant challenges in securing its vast maritime territory, requiring the integration of modern underwater technologies. While naval warfare increasingly relies on advanced systems, infrastructure limitations currently hinder the shift toward a cohesive, system-oriented undersea defense framework. Purpose. This study explores how underwater technology development can transform the Indonesian Navy’s strategic capabilities. It evaluates the potential of various assets to enhance operational effectiveness and aims to provide a modernization roadmap for the nation's maritime defense. Method. Using a mixed-methods design, the research combines quantitative surveys and qualitative case studies. This approach assesses the technical performance and organizational readiness of specific assets, including submarines, sonar systems, and unmanned underwater vehicles (UUVs). Results. Findings show that while submarines and sonar are well-integrated, UUVs face major operational hurdles due to technical gaps and poor system synergy. This suggests that technological innovation must be supported by a unified framework and specialized personnel training. Conclusion. Successful transformation depends on overcoming integration challenges and effectively deploying UUVs alongside traditional assets. The research recommends a balanced focus on both technological advancement and human resource development to ensure a secure and unified maritime future.